2021
DOI: 10.4103/joacp.joacp_35_20
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the time taken for subarachnoid block using ultrasound-guided method versus landmark technique for cesarean section – A randomized controlled study

Abstract: Background and Aims: Spinal anesthesia is the regional technique preferred for cesarean section and is usually administered using the traditional landmark technique. Ultrasonography of the spine appears to be helpful in locating the puncture site and increasing the success rate. The primary objective of this study was to assess the use of ultrasonogram in locating the lumbar interspinous space for spinal anesthesia in laboring parturients brought for elective cesarean section. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…US-guided spinal anaesthesia (SA) increases success at first pass and reduces the number of postoperative complications (postpartum backache and headache) and can be used for difficult spinal and as a routine practice in elective procedures. [ 13 , 14 ]…”
Section: Regional Anaesthesia For Caesarean Sectionmentioning
confidence: 99%
“…US-guided spinal anaesthesia (SA) increases success at first pass and reduces the number of postoperative complications (postpartum backache and headache) and can be used for difficult spinal and as a routine practice in elective procedures. [ 13 , 14 ]…”
Section: Regional Anaesthesia For Caesarean Sectionmentioning
confidence: 99%
“…[ 2 ] Randomised controlled trials (RCTs) and case reports have shown that pre-procedural US of the spine in the subarachnoid block and in the epidural catheter placement is particularly useful in obese parturients, parturients in labour, parturients with preeclampsia, and those with morbid obesity, spine disease, kyphoscoliosis, and on anticoagulants. [ 3 6 ] Pre-procedural USG in these cases provides information related to identification of the intervertebral levels, determination of needle insertion point, angle of needle trajectory, and depth of needle insertion. Needle insertion point in the midline can be obtained from the transverse interlaminar view with or without parasagittal oblique view.…”
Section: Advances In Regional Anaesthesia Techniques and Technologymentioning
confidence: 99%